Βιβλιοκρισία:D. SULLIVAN - A.-M. TALBOT - S. MCGRATH, The Life of Saint Basil the Younger. Critical Edition and Annotated Translation of the Moscow Version, Washington D.C. 2014 [Dumbarton Oaks Studies XLV), σελ. xii+829. ISBN 2013041388 - ΑΓΓΕΛΙΔΗ Χριστίνα (Byzantina Symmeikta, 2016)
Βιβλιοκρισία:D. Sullivan - A.-M. Talbot - S. McGrath, The Life of Saint Basil the Younger. Critical Edition and Annotated Translation of the Moscow Version, Washington D.C. 2014 [Dumbarton Oaks Studies XLV), σελ. xii+829. ISBN 2013041388